Respuestas
Respuesta dada por:
2
Resolver.
Aplicas productos notables.
(a - b)² = a² - 2ab + b²
(x - 2)² - (3 - x)² = 1
x² - 2(x)(2) + 2² - (3² - 2(3)(x) + x²) = 1
x² - 4x + 4 - ( 9 - 6x + x²) = 1
x² -4x + 4 - 9 + 6x - x² = 1
x² - x² - 4x + 6x + 4 - 9 = 1
2x - 5 = 1
2x = 1 +5
2x = 6
x = 6/2
x = 3
Respuesta.
x =3
Respuesta dada por:
2
Respuesta:
Explicación paso a paso:
(2x+1)x - 3^2=2(x+1)
2x(x) + 1(x) - 9 = 2x + 2
2x^2 + x - 9 = 2x + 2
2x^2 + x - 2x = 2 + 9
2x^2 - x = 11
Preguntas similares
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años